Monitoring Sistem Fluktuasi Harga Pangan Secara Realtime Berbasis Website - sari, dian megah (Universitas Multi Data Palembang, 2025)
The availability and access to sufficient, safe, and nutritious food is a fundamental human right. However, food price fluctuations are a key factor that significantly affect people's ability to meet their basic needs. Food price instability can result in various negative impacts, ranging from economic hardship to serious health problems. Monitoring food price fluctuations becomes crucial for governments, businesses, non-governmental organizations, and the general public to take appropriate steps in addressing the challenges faced. The aim of this research is to develop a system that monitors food price fluctuations as a key indicator of the development of the community's basic needs. The web-based system is developed using the PHP programming language with the open-source PHP framework Laravel as its platform, ensuring that food price information is presented transparently and is easily accessible to the public. Through this system, users can monitor changes in food prices over time, which can then be used as a basis for making economic decisions and managing household budgets.